2013
DOI: 10.3390/en6094429
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Peak-to-Peak Current Ripple Amplitude in Seven-Phase PWM Voltage Source Inverters

Abstract: Multiphase systems are nowadays considered for various industrial applications. Numerous pulse width modulation (PWM) schemes for multiphase voltage source inverters with sinusoidal outputs have been developed, but no detailed analysis of the impact of these modulation schemes on the output peak-to-peak current ripple amplitude has been reported. Determination of current ripple in multiphase PWM voltage source inverters is important for both design and control purposes. This paper gives the complete analysis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 29 publications
(51 reference statements)
0
11
0
Order By: Relevance
“…In particular, the analysis of the output current ripple amplitude in three-phase 2L inverters has been recently introduced in [13][14][15]. The extension to 2L multiphase inverters is given in [16][17][18], and compared in [19], whereas the extension to 3L three-phase inverters is given in [20] and [21]. In general, the knowledge of peak-to-peak current ripple amplitude in inverter motor drives allows one to optimize the switching frequency (and the associated losses), handle and minimize the acoustic noise, and mitigate the electromagnetic interference [17,22].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the analysis of the output current ripple amplitude in three-phase 2L inverters has been recently introduced in [13][14][15]. The extension to 2L multiphase inverters is given in [16][17][18], and compared in [19], whereas the extension to 3L three-phase inverters is given in [20] and [21]. In general, the knowledge of peak-to-peak current ripple amplitude in inverter motor drives allows one to optimize the switching frequency (and the associated losses), handle and minimize the acoustic noise, and mitigate the electromagnetic interference [17,22].…”
Section: Introductionmentioning
confidence: 99%
“…The survey in this sub-section has so far been related to output current THD and ripple rms squared value, which are important in order to predict the additional losses that will take place in a drive due to the inverter switching. A rather different type of study, related to the output current ripple peak-to-peak value, has been reported recently in [67][68][69]. Peak-to-peak current ripple amplitude is analytically determined as a function of the modulation index in [67] for the seven-phase two-level VSI with space vector PWM control.…”
Section: Evaluation Of the Current And Voltage Qualitymentioning
confidence: 99%
“…A rather different type of study, related to the output current ripple peak-to-peak value, has been reported recently in [67][68][69]. Peak-to-peak current ripple amplitude is analytically determined as a function of the modulation index in [67] for the seven-phase two-level VSI with space vector PWM control. It has been found that the value is practically linearly dependent on the value of the modulation index in the linear region.…”
Section: Evaluation Of the Current And Voltage Qualitymentioning
confidence: 99%
“…Likewise, as the freedom degrees number increases, the vector control gives more possibilities: the study of the current harmonic injection for higher torque density keeping a smooth torque [20][21][22][23][24][25][26]; the enlargement, for traction machines working in flux-weakening mode under voltage saturation [27][28][29][30][31], of the area of working. Finally, multi-leg Voltage Source Inverters (VSI) [32,33] present also numerous PWM(Pulse Width Modulation) control strategies.…”
Section: Introductionmentioning
confidence: 99%